Post-Contractual Non-Compete Clause in Commercial Agency Contracts - Kerčmar, Sebastjan (LeXonomica, 2025)
This paper deals with the legal regime governing post-contractual non-compete clauses in commercial agency contracts, analysing Slovenian legislation and its compliance with Directive 86/653/EEC. The Slovenian Obligations Code (OZ) requires the mandatory payment of compensation for compliance with a non-compete clause only in cases where the contract is terminated for reasons attributable to the principal. The author stresses that such a regime may lead to a restriction of contractual freedom without adequate compensation, which is not in line with the spirit of the Directive. Based on a review of the regimes in respect of non-compete clauses after the termination of a commercial agency contract in various European countries, including Croatia, the author finds that the regimes vary considerably between countries. The paper also focuses on the impact of non-compete clauses on indemnity, as the OZ requires such clauses to be taken into consideration in determining the amount. The author draws attention to the need for a fair balance of interests and for legislation to be revised to ensure that agents are protected against disproportionate restrictions without adequate compensation. Povzetek članka v slovenskem jeziku (abstract in Slovene language): Članek obravnava pravno ureditev konkurenčne klavzule po prenehanju pogodbe o trgovskem zastopanju, v okviru katere analizira slovensko zakonodajo in njeno skladnost z Direktivo 86/653/EGS. Slovenski Obligacijski zakonik (OZ) zahteva obvezno plačevanje odmene za spoštovanje konkurenčne klavzule zgolj v primerih, ko je pogodba prenehala zaradi razlogov na strani naročitelja. Po mnenju avtorja takšna ureditev lahko vodi v omejitev pogodbene svobode brez ustreznega plačila, kar ni v skladu z duhom direktive. Na podlagi pregleda ureditev konkurenčne klavzule po prenehanju pogodbe o trgovskem zastopanju v različnih evropskih državah, tudi na Hrvaškem, avtor ugotavlja, da se ureditev po posameznih državah zelo razlikuje. Avtor se osredotoča tudi na vpliv konkurenčne klavzule na odpravnino, saj OZ zahteva njeno upoštevanje pri določanju višine. Opozarja tudi na potrebo po pravičnem ravnotežju interesov in prilagoditvi zakonodaje, ki bi zagotavljala zaščito zastopnika pred nesorazmernimi omejitvami brez primernega nadomestila.